Bones of contention: the return of Nonteta, an Eastern Cape prophet - Edgar, Robert; Sapire, Hilary (My University, 1998)
Bones and burial places have been invested with special meanings in South Africa's recent political history. Before 1994 funerals of anti-apartheid martyrs often created public spaces for activists to renew resistance against the apartheid regime. Since 1994, the Truth and Reconciliation Commission has highlighted the iniquities of apartheid government hit squads by locating the graves of their victims and returning their remains to their families. However, as the public outcries over Saartje Baartman and Chief Hintsa indicate, the interest in the fate of remains extends back into previous centuries.
African Studies Seminar series. Paper presented 3 August, 1998
Keywords: Nkwenkwe, Nontetha,ca. 1875-1935; Women prophets. South Africa. Eastern Cape; Burial. South Africa. Eastern Cape; Anti-apartheid movements. South Africa